Fundamental Factors Bond Ratings: Modified Jones Model as Mediating Variable - Setiawati, Lilis; Putri, Uus Meilia; Mardiyani, Mardiyani (International Journal of Business, Economics, and Social Development, 2024)
The Study aims to ascertain how the debt-to-equity ratio, earnings management, and current ratio affect bond ratings in corporate businesses assessed by PT. PEFINDO 2020–2022 and listed on the Indonesia Stock Exchange. The reason earnings management is used as mediation in this research is a novelty from previous research, where earnings management is rarely used. The earnings management model used by the Jones modified has a higher level of accuracy compared to previous models, where the measurement is through revenue recognition which has the highest accuracy. Apart from that, many companies use earnings management practices so that the company's finances look good to investors, so the company will get new investors. In this study, 135 sample bond types that fit the predefined criteria were obtained from 26 organizations using purposive sampling with several preset criteria. Data analysis methods were uses path analysis techniques with the Lisrel program version 8.8 to analyze the available bond types. This study suggests that earnings management does not mediate between bond ratings and the current ratio. In particular, bond ratings are significantly impacted by the current ratio, the debt-to-equity ratio does not strongly impact earnings management, and bond ratings are not significantly affected by earnings management.